2009
DOI: 10.1007/s11033-009-9572-9
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between hemorheology and Glu(298)Asp polymorphism of endothelial nitric oxide synthase gene in patients with coronary artery disease

Abstract: This study aimed to investigate the relationship between endothelial nitric oxide synthase Glu(298)Asp gene polymorphism and hemorheological parameters. Red blood cell (RBC) deformability, aggregation were measured using an ectacytometry, whole blood, plasma viscosities were determined by a viscometer. Restriction fragment length polymorphism was used to detect polymorphism. Plasma nitrite, nitrate concentrations were determined by Griess method. The genotype distribution of the control group was as follows: 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 22 publications
2
12
0
Order By: Relevance
“…Our findings, in opposite, suggest that 298Arg ⁄ Arg genotype might be favourable for maintaining blood flow by causing decreased and slower erythrocyte aggregation. In concurrence with our findings, Bor-Kucukatay et al (2009) recently reported diminished erythrocyte aggregation with TT genotype in patients with coronary artery disease [18].…”
Section: Functional Effects Of Enos Genetic Variants In Human Erythrosupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings, in opposite, suggest that 298Arg ⁄ Arg genotype might be favourable for maintaining blood flow by causing decreased and slower erythrocyte aggregation. In concurrence with our findings, Bor-Kucukatay et al (2009) recently reported diminished erythrocyte aggregation with TT genotype in patients with coronary artery disease [18].…”
Section: Functional Effects Of Enos Genetic Variants In Human Erythrosupporting
confidence: 93%
“…The physiological consequences of eNOS genetic variability in erythrocyte rheology in human beings are largely unknown. Although few previous reports investigated the role of eNOS genetic variants on erythrocyte properties in microcirculatory disorders such as coronary artery disease, idiopathic sudden sensorineural hearing loss and systemic sclerosis, their results were inconclusive for physiological consequences of eNOS genetic polymorphisms in healthy individuals [16][17][18].Blood viscosity is determined by four parameters: haematocrit levels, erythrocyte aggregability, erythrocyte deformability and plasma viscosity [19]. Decrease in the deformability of erythrocytes or increase either in erythrocyte aggregation, plasma viscosity or haematocrit result in a higher blood viscosity.…”
mentioning
confidence: 99%
“…It is worthy to note that increments in amplitude of the aggregation and aggregation index and decrement of t 1/2 are concordant with each other and indicate increment of RBC aggregation. The discussion whether alterations in haemorrheological parameters are the cause or the result of some systemic diseases, such as hypertension and coronary artery disease still goes on in the literature . Our experiments do not enlighten this issue directly for POAG because glaucoma is a local disease and far from affecting the determinants of RBC aggregation systemically.…”
Section: Discussionmentioning
confidence: 78%
“…Meta-analysis of clinical studies suggests that the eNOS gene polymorphisms could have a more predictive value in certain ethnic populations with specified cardiovascular risk factor profiles (Table 5) (Hingorani et al, 1999;Sigusch et al, 2000;Granath et al, 2001;Wang et al, 2001;Colombo et al, 2002;Afrasyap et al, 2004;Kerkeni et al, 2006;Yang and Ming, 2006;Angeline et al, 2010;Bor-Kucukatay et al, 2010;Isordia-Salas et al, 2010;Abdel Aziz et al, 2013).…”
Section: Discussionmentioning
confidence: 99%